Effect of Methanol Concentration and Channel Depth on Performance of Direct Methanol Fuel Cell - Ebrahim Alizadeh; Kourosh Sedighi; Mousa Farhadi; Mohsen Shakeri (International Journal of Advanced Design and Manufacturing Technology, 2010)
Effect of methanol concentration and channel depth of bipolar plates on the performance of single direct methanol fuel cell was investigated experimentally. The membrane used in this experiment was Nafion117. Dimension of the single cell were 10cm 10 cm. Methanol concentrations of 0.50, 1.0, 1.5, 2.0, 3.0 molar were used. Channel depth of the bipolar plates were chosen to be 1.0, 1.5, 2.0 mm, and in order to investigate the effect of channel depth, anode channel depth and cathode depth were changed simultaneously. Optimized methanol concentration for the single cell were 0.5-1.5 molar. Based on different experiments, as channel depth is decreased, mass transfer is improved and removal of carbone dioxide takes place easier. The results indicate that the best channel depth for this kind of single cell is 1.0 mm.